2009
DOI: 10.1371/journal.pone.0007309
|View full text |Cite
|
Sign up to set email alerts
|

Aldo Keto Reductase 1B7 and Prostaglandin F2α Are Regulators of Adrenal Endocrine Functions

Abstract: Prostaglandin F2α (PGF2α), represses ovarian steroidogenesis and initiates parturition in mammals but its impact on adrenal gland is unknown. Prostaglandins biosynthesis depends on the sequential action of upstream cyclooxygenases (COX) and terminal synthases but no PGF2α synthases (PGFS) were functionally identified in mammalian cells. In vitro, the most efficient mammalian PGFS belong to aldo-keto reductase 1B (AKR1B) family. The adrenal gland is a major site of AKR1B expression in both human (AKR1B1) and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…However, there is no report on the detailed properties of AKR1B14, except for its role as a PGF 2a synthase in rat adrenal cells. 23) Recently, we have established the bacterial overexpression system of recombinant AKR1B14, which provided high yield of the enzyme and subsequently lead to successful crystallisation attempts. 24) In this study, we examined the substrate specificity of recombinant AKR1B14 in both the reduction and oxidation directions in order to elucidate the enzyme function related to the hepatic expression induced by oxidative stress.…”
mentioning
confidence: 99%
“…However, there is no report on the detailed properties of AKR1B14, except for its role as a PGF 2a synthase in rat adrenal cells. 23) Recently, we have established the bacterial overexpression system of recombinant AKR1B14, which provided high yield of the enzyme and subsequently lead to successful crystallisation attempts. 24) In this study, we examined the substrate specificity of recombinant AKR1B14 in both the reduction and oxidation directions in order to elucidate the enzyme function related to the hepatic expression induced by oxidative stress.…”
mentioning
confidence: 99%
“…By using their purified recombinant proteins, we recently demonstrated that several members of the AKR1B family, such as human AKR1B1, mouse AKR1B3, and bovine AKR1B5, have PGFS activity higher than that of AKR1C3 (30). Among those members of the AKR1B family, AKR1B7 was demonstrated by Lambert-Langlais et al (31) to be involved in the production of PGF 2␣ in adrenal glands for inhibition of glucocorticoid secretion. Tirard et al (32) previously reported that overexpression of Akr1b7 suppressed lipid accumulation in transfected 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Akr1b7 participates in steroid synthesis in the adrenal gland, where renin is also expressed in fetal life. 28 Most recently, Akr1b7 has been shown to be crucial in the synthesis of prostaglandins, 29 which, in turn, are known to regulate renin synthesis and release, 1 suggesting that AKR1B7 may regulate renin release by an intracrine mechanism. Further studies will be necessary to determine the role of Akr1b7 in renin cells.…”
Section: Novel Features Of the Present Work Include The Extensive Commentioning
confidence: 99%